Effects of Screw and Plate Positions in the Dual Plating of Distal Humerus Fixation - Hakim Noordin, Luqman; Hisyam Marwan, Shahrul; Halim Abdullah, Abdul (International Journal of Engineering and Technology, 2018)
Bone fractures are one of the common effects of road accident. Osteosynthesis is a surgical procedure to treat the fractures of the bones by inserting implant to restore the fracture bones to its original position and immobilizing the restored region to allow proper growth of bone. One of the main problems of an internal fixation surgery is the ability of implants to retain the original position of humerus bone without any other complications during the fractured bone development. Thus, the purposes of the study was to analyze the biomechanical effects of screw and plate positioning at the distal humerus bone. The static analysis is carried out to evaluate the effect of mechanical characteristics and stress distribution in the humerus bone by using computational design and analysis software (CATIA) and Materialise Interactive Medical Image Control System (MIMICS) software. Thus, the analysis resulted to stress/strain distributions and displacement of the humerus bone and dual plate implant respectively. Different positioning of screws shows more significant results compared to positioning of dual locking plate regarding to the stress distribution and displacement of locking plate implant which can lead to disturbance towards the growth of bone.Â Â